Properties of moisture tolerant perovskite solar cells wherein a 3D perovskite is encapsulated by long-chain alkylammonium cation-based 2D perovskites - Properties of moisture tolerant solar cells by encapsulating 3D perovskite with long-chain alkylammonium cation-based 2D perovskites - Gardner, James (Royal Institute of Technology, 2021)
The data are associated with the open access article "Moisture tolerant solar cells by encapsulating 3D perovskite with long-chain alkylammonium cation-based 2D perovskite" published in "Communications Materials" in 2021. The data are X-ray diffraction patterns, UV-Visible absorption spectra, time-resolved photoluminescence, solar cell performance parameters, electrical parameters, and chemical stability of hybrid organic lead(II) iodide perovskite materials with long alkyl chains (C14-C18). The DOI for the original scientific article is: 10.1038/s43246-021-00200-8.

Data associeras med artikeln "Moisture tolerant solar cells by encapsulating 3D perovskite with long-chain alkylammonium cation-based 2D perovskite" som publiceras i tidskriften "Communications Materials" under 2021. Data är röntgendiffraktionsmönster, UV-Vis absorptionsspektra, tidsupplöst fotoluminescens, solcellsparametrar, elektriska parametrar och kemisk stabilitet av hybrid organisk bly(II) jodid perovskitmaterial med långa alkylkedjor (C14-C18). Den vetenskapliga artikelns DOI är: 10.1038/s43246-021-00200-8.
Egenskaper hos fukt-toleranta perovskitsolceller där 3D-perovskit kapslats in med lång-kedje-alkylammonium katjonbaserad 2D perovskit - Egenskaper hos fukttåliga solceller från inkapslande 3D perovskiter med lång kedja alkylammonium katjon-baserade 2D perovskiter
Keywords: solar energy; solenergi; Perovskite; Perovskit; Physical Chemistry; Fysikalisk kemi; Materials Chemistry; Materialkemi; Inorganic Chemistry; Oorganisk kemi